Anti-Aminoacyl Transfer-RNA-Synthetases (Anti-tRNA) Autoantibodies Associated with Interstitial Lung Disease: Pulmonary Disease Progression has a Persistent Elevation of the Th17 Cytokine Profile - Ramos-Martinez, Espiridión (J Clin Med, 2020)
Anti-tRNA autoantibodies are associated with interstitial lung disease (ILD), in at least two clinical scenarios: the anti-synthetase syndrome (ASSD) and interstitial pneumonia with autoimmune features (IPAF). Under pathological conditions, cytokines indicate the participating elements and the course of inflammatory phenomena. We aimed to quantify serum concentrations of different inflammatory cytokines profiles in patients with anti-tRNA associated ILD (anti-tRNA-ILD) and estimate the association between these and ILD improvement and progression. Serum levels of 18 cytokines from baseline and after six months of treatment of ILD patients’ positives to anti-tRNA were included in the current study. At six months, patients were classified as with or without ILD progression. A total of 39 patients were included (10 anti-Jo1, eight anti-PL7, 11 anti-PL12, and 10 anti-Ej). Three patients (7.6%) had ILD progression (progressors patients, PP) and showed statistically higher levels in IL-4, IL-10, IL-17A, IL-22, GM-CSF, IL-1β, IL-6, IL-12, IL-18, and TNF-α, compared to patients without disease progression (no progressors patients, NPP). IL-17A, IL-1β, and IL-6 (T-helper-lymphocyte (Th)17 inflammatory cytokine profile) were elevated and had a high discriminatory capacity in distinguishing ILD PP of those NPP at follow-up. Overall, there is an association between the cytokines of the Th17 inflammatory profile and the ASSD progression.